Electronic and optical properties of titanium nitride bulk and surfaces from first principles calculations - Mehmood, Faisal; Pachter, Ruth; Murphy, Neil R.; Johnson, Walter E. (Journal of applied physics, 2015)
Prediction of the frequency-dependent dielectric function of thin films poses computational challenges, and at the same time experimental characterization by spectroscopic ellipsometry remains difficult to interpret because of changes in stoichiometry and surface morphology, temperature, thickness of the film, or substrate. In this work, we report calculations for titanium nitride (TiN), a promising material for plasmonic applications because of less loss and other practical advantages compared to noble metals. We investigated structural, electronic, and optical properties of stoichiometric bulk TiN, as well as of the TiN(100), TiN(110), and TiN(111) outermost surfaces. Density functional theory (DFT) and many-body GW methods (Green's (G) function-based approximation with screened Coulomb interaction (W)) were used, ranging from G0W0, GW0 to partially self-consistent sc-GW0, as well as the GW-BSE (Bethe-Salpeter equation) and time-dependent DFT (TDDFT) methods for prediction of the optical properties. Structural parameters and the band structure for bulk TiN were shown to be consistent with previous work. Calculated dielectric functions, plasma frequencies, reflectivity, and the electron energy loss spectrum demonstrated consistency with experiment at the GW0-BSE level. Deviations from experimental data are expected due to varying experimental conditions. Comparison of our results to spectroscopic ellipsometry data for realistic nanostructures has shown that although TDDFT may provide a computationally feasible level of theory in evaluation of the dielectric function, application is subject to validation with GW-BSE calculations.